Distribution of non-lumbricid earthworms (Clitellata: Acanthodrilidae, Criodrilidae, Megascolecidae and Ocnerodrilidae) on the Balkans and Anatolia with first record of Amynthas morrisi (Beddard, 1892) from Turkey - Misirlioğlu, İbrahim Mete; Stojanović, Mirjana (Zootaxa, 2018)
Based on previous and on new species records, the non-lumbricid earthworm fauna of the Balkans and Anatolia consists of ten species, belonging to four families: Acanthodrilidae, with Microscolex dubius (Fletcher, 1886) and Microscolex phosphoreus (Dugès, 1837), Criodrilidae, with Criodrilus lacuum Hoffmeister, 1845 and Criodrilus ochridensis Georgevitch, 1950, Megascolecidae, with Amynthas corticis (Kinberg, 1867), Amynthas gracilis (Kinberg, 1867), Amynthas morrisi (Beddard, 1892), Metaphire californica (Kinberg, 1867), and Pontodrilus litoralis (Grube, 1855), and Ocnerodrilidae, with Ocnerodrilus occidentalis Eisen, 1878. Four species are recorded on the both territories (C. lacuum, M. dubius, M. phosporeus, A. corticis). Four out of five megascolecid species are present in Turkey (A. corticis, A. gracilis, A. morrisi, M. californica) and only two (A. corticis, P. litoralis) in the Balkans. One of them, Amynthas morrisi, is new to the fauna of Turkey.